Bio-enzyme for catalyzing and slowly releasing bio-energy substances and immobilization method of bio-enzyme
By loading dopamine and starch glucosidase on the ceramic matrix, combined with coaxial 3D printing technology, the sustained release of glucose in the bone defect area is achieved, solving the problem of obstruction of bioenergy material delivery channels and improving the effect of bone repair.
Patent Information
- Application Number
- CN202411878986.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the application of traditional bone repair materials in the bone defect area, the delivery channels of bioenergy substances are blocked, resulting in the lack of necessary nutritional support for tissues and cells in the bone defect site, affecting the bone repair effect.
The in-situ catalytic sustained release of glucose is achieved by using a ceramic matrix to support dopamine and starch glucosidase biological enzyme, and a coaxial scaffold is prepared in combination with coaxial 3D printing method to extend the glucose sustained release time.
It significantly improves the stability of biological enzymes, extends the delayed release time of glucose, promotes the proliferation of bone marrow mesenchymal stem cells, and improves the effect of bone repair.
Smart Images

Figure CN119736278A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tissue engineering and bone repair, and specifically relates to a biological enzyme for catalyzing the slow release of biological energy substances and a fixation method thereof. Background Art
[0002] Bone defects caused by infection, trauma and various diseases (such as osteonecrosis, osteoporosis and bone tumors) pose a serious threat to the health and quality of life of patients. Traditional bone repair materials mainly release Ca 2+ PO4 3- Mg 2+ and Zn 2+ Plasma is used to promote cell differentiation and activate related cell pathways, thereby promoting the repair process of bone tissue. However, bone defect areas are often accompanied by severe damage to the blood supply, which leads to obstruction of the delivery channels of bioenergy substances (including glucose, fatty acids and amino acids, etc.), resulting in a lack of necessary nutritional support for tissues and cells in the bone defect site, which ultimately affects the effect of bone repair. Cells obtain adenosine triphosphate (ATP) by breaking down glucose, fatty acids and amino acids obtained from food or stored in the body to meet the normal energy needs of cells, and glucose is the preferred energy substance for most cells in the body. Therefore, slow release of glucose directly at the defect is the best choice to solve the lack of nutrients in bone defects, especially in the early stages.
[0003] Bioenzymes are organic substances with catalytic functions produced by living cells. They can significantly reduce the activation energy of chemical reactions, thereby accelerating the rate of chemical reactions. Depending on the substrate and the type of catalytic reaction, bioenzymes can be further divided into various types, such as pectinase, lipase, amylase, cellulase, etc. Bioenzymes have the advantages of high catalytic activity, fast catalytic efficiency, reaction specificity, small dosage and mild reaction conditions. They are widely used in the fields of pharmaceuticals, cosmetics, pulp, biofuels, textiles, food, water treatment, petroleum, brewing and biomedicine.
[0004] The glucose needed by the human body usually exists in food in the form of carbohydrates (such as starch). Carbohydrate-rich foods, such as rice, pasta, bread, fruits and vegetables, are important sources of glucose. When the human body ingests these foods, the digestive system will use a variety of biological enzymes (salivary amylase, pancreatic amylase and intestinal starch) to break them down into glucose monosaccharides, which are then absorbed into human tissues to provide energy. Therefore, biological enzymes can be used to achieve in-situ catalytic slow release of glucose to solve the problem of energy deficiency in bone defects.
[0005] Studies have found that amyloglucosidase can catalyze starch to produce glucose monosaccharides. However, its application currently faces the problem of poor stability: the activity of biological enzymes is easily disturbed by various factors, such as temperature, various salts in the solution and their concentrations and pH changes, etc. These factors may cause the structure of the biological enzyme to change, thereby losing its catalytic activity. In addition, over time, it is also easy to inactivate and lose its catalytic activity due to its own structural instability. Therefore, how to improve the stability of biological enzymes is crucial. Summary of the invention
[0006] In view of the technical problem that amyloglucosidase has poor stability, the object of the present invention is to provide a method for fixing amyloglucosidase to improve its stability.
[0007] In a first aspect, the present invention provides a biological enzyme for catalyzing the slow release of bioenergy substances, the biological enzyme for catalyzing the slow release of bioenergy substances comprising: a ceramic matrix, dopamine loaded on the ceramic matrix, and amyloglucosidase loaded on the dopamine; Taking the total mass of the biological enzyme for catalyzing the slow release of bioenergy substances as 100%, the mass of the ceramic matrix accounts for 80-90%, the mass of dopamine accounts for 5-10%, and the mass of amyloglucosidase accounts for 1-10%.
[0008] Preferably, the ceramic matrix is at least one of hydroxyapatite, β-TCP, and dicalcium silicate, preferably β-TCP.
[0009] In a second aspect, the present invention provides a method for fixing the above-mentioned biological enzyme for catalyzing the slow release of biological energy substances, the fixing method comprising the following steps: (1) mixing ceramic powder and dopamine hydrochloride to obtain a raw material mixed powder, and then adding deionized water thereto and stirring to obtain a dopamine-loaded ceramic powder; (2) The dopamine-loaded ceramic powder is mixed with amyloglucosidase, and then deionized water is added and shaken to mix, so that the amyloglucosidase is fully loaded and bound to the dopamine, thereby obtaining the fixed biological enzyme for catalyzing the slow release of bioenergy substances.
[0010] Preferably, in step (1), the particle size of the ceramic powder is 100nm-10μm, preferably 300nm-10μm, and the specific surface area is 10-50m 2 / g.
[0011] Preferably, in step (1), the mass ratio of the ceramic powder to dopamine hydrochloride is 5-10:1.
[0012] Preferably, in step (1), the ratio of the raw material mixed powder to deionized water is 1g:5-10mL.
[0013] Preferably, in step (2), the mass ratio of the dopamine-loaded ceramic powder to amyloglucosidase is 1:0.1-0.4.
[0014] Preferably, in step (2), the dosage ratio of the dopamine-loaded ceramic powder to deionized water is 1 g:5-50 mL, preferably 1 g:20-50 mL.
[0015] Beneficial Effects The present invention significantly improves the stability of the biological enzyme by fixing amyloglucosidase; at the same time, the coaxial stent is prepared by a coaxial 3D printing method using the fixed biological enzyme. Since the coaxial stent has a longer glucose sustained-release effect, the proliferation of bone marrow mesenchymal stem cells is promoted. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Characterization of the immobilization of amyloglucosidase in Example 1: (a) and (b) are SEM morphologies of β-TCP powder after grinding, (c) and (d) are SEM morphologies of β-TCP powder loaded with dopamine, and (e) and (f) are SEM morphologies of β-TCP powder loaded with amyloglucosidase; Figure 2 Characterization of the amyloglucosidase loading in Example 1: (a) and (b) are schematic diagrams of the particle size distribution and specific surface area of β-TCP powder after grinding, and (c) and (d) are XRD and Raman characterizations of β-TCP powder under different loadings; Figure 3 The performance characterization of amyloglucosidase before and after immobilization: (a) is the absorbance after the reaction of different concentrations of glucose solution with DNS, (b) is the curve of the relationship between absorbance and concentration, (c) is the schematic diagram of the activity of amyloglucosidase and its loading after immobilization, and (d) is the activity curve of amyloglucosidase at different immersion times after immobilization; Figure 4 Coaxial 3D printed scaffolds with PCL / β-TCP as the outer layer: (A) is a solid structure scaffold (Control), (B) is an inner layer pure starch material (STA) scaffold, (C) is an inner layer starch material containing glucose (GLU) scaffold, (D) is an inner layer starch material containing 2% TDA (2% TDA) scaffold, (E) is an inner layer starch material containing 5% TDA (5% TDA) scaffold, (F) is an inner layer starch material containing 10% TDA (10% TDA) scaffold; Figure 5 This is the glucose release curve of the coaxial scaffold; Figure 6Schematic diagram of rBMSCs cell proliferation and adhesion on the scaffold: (A) is the cell proliferation represented by the absorbance of the microplate reader, (B) is the fluorescence imaging of cell morphology, and (C) is the SEM morphology of the cells. DETAILED DESCRIPTION
[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0018] First, the present invention provides a biological enzyme for catalyzing the slow release of bioenergy substances, wherein the biological enzyme for catalyzing the slow release of bioenergy substances comprises: a ceramic matrix, dopamine loaded on the ceramic matrix, and amyloglucosidase loaded on the dopamine.
[0019] In some embodiments, the ceramic matrix may be at least one of hydroxyapatite, β-TCP and dicalcium silicate, preferably β-TCP (Chinese: β-tricalcium phosphate).
[0020] Among them, nano-scale lath-like hydroxyapatite will be generated on the surface of β-TCP during the grinding process, which further increases its specific surface area and is beneficial to dopamine loading.
[0021] In some embodiments, based on the total mass of the bio-enzyme for catalyzing the slow release of bioenergy substances as 100%, the mass of the ceramic matrix may account for 80-90%, the mass of dopamine may account for 5-10%, and the mass of amyloglucosidase may account for 1-10%.
[0022] Among them, if the overall mass of the ceramic accounts for too large a proportion, the dopamine loading will be low, thus affecting the loading of amyloglucosidase; if the mass of dopamine accounts for too large a proportion, it will not be fully loaded on the ceramic particles, causing waste, and a thicker dopamine layer will be generated, affecting the loading; if the mass of the biological enzyme accounts for too large a proportion, it will be difficult to fully load it, resulting in substantial waste.
[0023] The following is an exemplary description of the method for fixing a biological enzyme for catalyzing the slow release of biological energy substances provided by the present invention. The fixing method may include the following steps: (1) mixing ceramic powder and dopamine hydrochloride to obtain a raw material mixed powder, then adding deionized water thereto and magnetically stirring for 1-4 hours, centrifuging, washing with deionized water, and freeze-drying to obtain a dopamine-loaded ceramic powder; (2) The dopamine-loaded ceramic powder is mixed with amyloglucosidase, and then deionized water is added and shaken for 4-12 hours to allow the amyloglucosidase to be fully loaded and bound to the dopamine. After washing and drying, a fixed bioenzyme for catalyzing the slow release of bioenergy substances is obtained.
[0024] In some embodiments, in step (1), the particle size of the ceramic powder can be 100 nm-10 μm, preferably 300 nm-10 μm, and the specific surface area is 10-50 m 2 / g.
[0025] If the particle size of ceramic powder is too large, the specific surface area of the particles will be small, and the final enzyme load will be less; if the particle size of ceramic powder is too small, its specific surface area will be large, but it will be easy to agglomerate. By selecting a suitable method to generate nanostructures on the surface of medium particles, the agglomeration problem can be avoided while ensuring the specific surface area of the powder.
[0026] In some embodiments, in step (1), the mass ratio of the ceramic powder to dopamine hydrochloride can be 5-10:1.
[0027] In some embodiments, in step (1), the usage ratio of the raw material mixed powder to deionized water can be 1 g: 5-10 mL.
[0028] In some embodiments, in step (2), the mass ratio of the dopamine-loaded ceramic powder to the amyloglucosidase can be 1:0.1-0.4. If the amount of amyloglucosidase is too large, some biological enzymes cannot be successfully loaded and cannot play a catalytic role, resulting in waste; if the amount of amyloglucosidase is too small, the ceramic particles will be insufficiently loaded, affecting the final catalytic effect.
[0029] In some embodiments, in step (2), the dosage ratio of the dopamine-loaded ceramic powder to deionized water may be 1 g:5-50 mL, preferably 1 g:20-50 mL.
[0030] The glucose concentration can be quantitatively determined using 3,5-dinitrosalicylic acid colorimetry and UV-visible absorption spectrometer. The specific determination method is as follows: take 1g of starch, dissolve it in 100ml of deionized water, and heat it to boil; after the starch solution cools, add 0.01-0.1g of fixed and unfixed enzymes and react for 30 minutes; use the DNS method to determine the glucose concentration of the starch solution, then calculate the true activity of the fixed enzyme and the unfixed enzyme, and obtain the fixed loading amount of the amyloglucosidase; then determine the relative activity of the fixed enzyme and the unfixed enzyme in an environment of 37°C and pH=7.4 to evaluate the effect of fixation on the activity.
[0031] Using the method disclosed in patent ZL202110277324.X, a coaxial scaffold with starch-immobilized amyloglucosidase as the inner layer and β-TCP / PCL as the outer layer was printed to study the glucose release performance of the coaxial scaffold: The coaxial stent was placed in a centrifuge tube and PBS solution was added. Samples were taken regularly and new immersion solution was replaced at a preset time. The glucose release curve of the coaxial stent at different times at 37°C was measured to evaluate the glucose release performance of different coaxial stents.
[0032] In addition, bone marrow mesenchymal stem cells can be cultured using the above coaxial scaffolds to study the effects of the coaxial scaffolds on their proliferation.
[0033] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0034] Example 1
[0035] The method for fixing the biological enzyme for catalyzing the slow release of biological energy substances provided in this embodiment comprises the following steps: (1) Using a planetary ball mill, β-TCP powder was ground in an aqueous solution for 24 h to obtain a smaller particle size (MillingTCP, T), and its particle size and specific surface area were characterized using a laser particle size analyzer and a specific surface area pore size analyzer; the ground β-TCP powder was mixed with dopamine hydrochloride at a mass ratio of 10:1; deionized water was then added at a ratio of 10 ml / g powder, and magnetic stirring was performed at room temperature for 4 h; the dopamine-loaded β-TCP powder was centrifuged and washed 3 times using a centrifuge and deionized water, respectively, and the dopamine-loaded ceramic powder was obtained after freeze-drying (Milling TCP-Dopa, TD); (2) Mix according to the ratio of 1 g TD powder / 0.2 g amyloglucosidase, and add deionized water according to the ratio of 5 ml deionized water / 1 g powder, shake in an oscillator for 12 h to fully load the amyloglucosidase, and finally centrifuge and wash 3 times, and freeze-dry the sample to obtain a fixed bioenzyme (MillingTCP-Dopa-AGS, TDA) for catalyzing the slow release of bioenergy substances.
[0036] X-ray diffractometer (XRD), scanning electron microscope (SEM), Raman spectrometer (Raman) were used to characterize the crystal structure, micromorphology and functional groups of the β-TCP powder (T), dopamine-loaded β-TCP powder (TD) and amyloglucosidase-loaded β-TCP powder (TDA) prepared in Example 1 to determine the loading of the enzyme, see Appendix Figure 1 and 2 .from Figure 1 , 2 It can be seen that nano-scale lath-shaped hydroxyapatite is generated on the ground β-TCP, and the particle size distribution and specific surface area of the ground particles are 300nm-10μm and 31.132m 2 / g; XRD and Raman tests showed that dopamine and amyloglucosidase were successfully loaded on the ceramic particles.
[0037] The following uses 3,5-dinitrosalicylic acid colorimetry and UV-visible absorption spectrometer to quantitatively determine the glucose concentration: first, prepare a glucose solution with a concentration of 1 mg / ml, and then prepare glucose solutions with concentrations of 0.2, 0.4, 0.6 and 0.8 mg / ml based on this; take 0.5 ml of the above glucose solution and add it to 15 ml centrifuge tubes, and then add 0.5 ml DNS solution; the centrifuge tubes are placed in a boiling water bath for 10 minutes, taken out and cooled for testing; take 0.3 ml of the reaction solution and add it to a cuvette, and dilute it to 3 ml with deionized water; use a UV-visible spectrophotometer to measure the absorption spectra of glucose solutions of different concentrations at 400-700 nm, and measure each group of samples 3 times; count the highest absorbance value of each curve and draw an absorbance-concentration standard curve; in the subsequent test process, if the measured glucose concentration is higher than 1 mg / ml, it needs to be diluted proportionally to the range of 0-1 mg / ml.
[0038] Take 1g starch, dissolve it in 100ml deionized water, and heat it to boil; after the starch solution is cooled, add 0.01g fixed and unfixed enzymes and react for 30min; use the DNS method to determine the glucose concentration of the starch solution, and then calculate the true activity of the fixed enzyme and the unfixed enzyme, and obtain the fixed loading amount of the amyloglucosidase; then determine the relative activity of the fixed enzyme and the unfixed enzyme at 37°C and pH=7.4 for 1, 3, 7, 14, 21 and 28 days to evaluate the effect of fixation on the activity.
[0039] Figure 3The performance of amyloglucosidase before and after fixation is characterized as follows: (a) is the absorbance after the reaction of different concentrations of glucose solution with DNS, (b) is the curve of absorbance and concentration, (c) is the schematic diagram of the activity of amyloglucosidase and its loading after fixation, and (d) is the activity curve of amyloglucosidase at different immersion times after fixation. As can be seen from the figure, since the absorbance has a high linear relationship with the glucose concentration, the DNS method can be used to reverse the glucose concentration of the solution. The activity of the ceramic particles loaded with amyloglucosidase is 110U / g. The fixed amyloglucosidase has higher stability and sustained catalytic activity than the unfixed one.
[0040] The starch slurry was prepared by high-temperature boiling method, and different proportions of fixed amyloglucosidase (TDA) were evenly added to the starch slurry at low temperature. The specific process is: take 1g, 1g, 0.98g, 0.95g and 0.9g starch, respectively, and add them to beakers; add 10g water to the beaker, and then boil the starch solution under magnetic stirring until it becomes a viscous and clear slurry; after the starch slurry is cooled, 1g anhydrous glucose, 0.02g TDA, 0.05gTDA and 0.1g TDA are added to the above beakers starting from the second beaker. Add an appropriate amount of deionized water to all beakers so that the total mass of starch (+TDA) and deionized water is 5g. Stir the slurry in the above beakers evenly and transfer it to the barrel for standby. They are numbered STA, GLU, 2% TDA, 5% TDA and 10% TDA respectively. The glucose release curve in patent ZL202110277324.X is basically similar to that of the GLU group, so GLU is used to replace this group of data.
[0041] Figure 4 The coaxial 3D printed scaffolds with PCL / β-TCP as the outer layer: (A) is a solid structure scaffold (Control), (B) is a scaffold with pure starch material (STA) in the inner layer, (C) is a scaffold with starch material (GLU) containing glucose in the inner layer, (D) is a scaffold with starch material (2% TDA) containing 2% TDA in the inner layer, (E) is a scaffold with starch material (5% TDA) containing 5% TDA in the inner layer, and (F) is a scaffold with starch material (10% TDA) containing 10% TDA in the inner layer. It can be seen from the figure that except for the Control group, the other groups are coaxial structures, there are no particles in the starch layer of the STA and GLU groups, and there is a significant increase in the number of starch layer particles in the 2%-10% TDA group.
[0042] Figure 5 This is the glucose release curve of the coaxial stent. As can be seen from the figure, the GLU group has basically released all the glucose on the third day; the other groups containing fixed biological enzymes all showed a longer sustained release time, and with the increase of fixed biological enzymes, the total glucose sustained release also showed an increasing trend.
[0043] Cell proliferation was determined using the Cell Counting Kit-8 (CCK-8) method. In the experiment, coaxial scaffolds with inner layers containing no starch (solid structure), pure starch, starch containing glucose, starch containing 2% TDA, starch containing 5% TDA, and starch containing 10% TDA were set as experimental groups and named Control, STA, GLU, 2% TDA, 5% TDA, and 10% TDA, respectively. First, the scaffolds used in the cell experiment were soaked in 75% ethanol for half an hour and washed with sterile PBS buffer for 3-5 times, each time for 5 minutes; then, the treated scaffolds were added to the 48-well plate and inoculated with 1×10 4 rBMSCs cells were cultured at 37°C, 5% CO2 and 95% humidity for 1, 3 and 7 days; the medium was changed once on the 3rd and 5th days, respectively. Then, CCK-8 working solution diluted 10 times with pure DMEM was added to each well containing the scaffold and continued to be cultured for 2 hours, and the solution was transferred to a new 96-well plate by aspiration; finally, the OD value of the solution at 450nm was measured by an ELISA instrument (six parallel samples in each group) to evaluate the effect of the coaxial scaffold on the proliferation of rBMSCs cells. First, the cultured rBMSCs were digested with trypsin and centrifuged at 1000 rpm for 5 min. The cells were diluted with the corresponding culture medium and counted. The six groups of scaffolds, Control, STA, GLU, 2% TDA, 5% TDA and 10% TDA, were placed in a 48-well plate at 1×10 per well. 5 Cell implantation. The cells were cultured in an environment of 37°C, 5% CO2 and 95% humidity for 3 days, and the culture medium was aspirated. Use 2.5% glutaraldehyde to fix for 2 hours, then aspirate the glutaraldehyde solution and wash 3 times with PBS. The fixed samples were immersed in 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% and 100% ethanol solutions for 3 times, 10 minutes each time, and gradually dehydrated. Then the samples were treated with 50% hexamethyldisilazane / ethanol solution for 10 minutes, and finally the samples were immersed in 100% hexamethyldisilazane solution for 10 minutes, placed in a fume hood to dry overnight, and used for SEM to observe the adhesion behavior of the cells.
[0044] Figure 6Schematic diagram of rBMSCs cell proliferation and adhesion on the scaffold: (A) is the cell proliferation represented by the absorbance of the microplate reader, (B) is the cell morphology fluorescence imaging, and (C) is the cell SEM morphology. It can be seen from the figure that on the first day, there was no significant difference, and the GLU group showed an inhibitory effect; on the third day, the fixed bioenzyme group showed higher cell proliferation, but too much glucose release would affect cell viability; the results on the seventh day were basically consistent with those on the third day; the cell adhesion SEM image and cell staining image were basically consistent with the cell proliferation results on the third day.
[0045] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A biological enzyme for catalyzing the slow release of bioenergy substances, characterized in that: The biological enzyme for catalyzing the slow release of bioenergy substances comprises: a ceramic matrix, dopamine loaded on the ceramic matrix, and amyloglucosidase loaded on the dopamine; Taking the total mass of the biological enzyme for catalyzing the slow release of bioenergy substances as 100%, the mass of the ceramic matrix accounts for 80-90%, the mass of dopamine accounts for 5-10%, and the mass of amyloglucosidase accounts for 1-10%.
2. The biological enzyme for catalyzing the slow release of bioenergy substances according to claim 1, characterized in that: The ceramic matrix is at least one of hydroxyapatite, β-TCP, and dicalcium silicate, preferably β-TCP.
3. A method for fixing a biological enzyme for catalyzing and slowly releasing biological energy substances according to claim 1 or 2, the method comprising the following steps: (1) mixing ceramic powder and dopamine hydrochloride to obtain a raw material mixed powder, and then adding deionized water thereto and stirring to obtain a dopamine-loaded ceramic powder; (2) The dopamine-loaded ceramic powder is mixed with amyloglucosidase, and then deionized water is added and shaken to mix, so that the amyloglucosidase is fully loaded and bound to the dopamine, thereby obtaining the fixed biological enzyme for catalyzing the slow release of bioenergy substances.
4. The fixing method according to claim 3, characterized in that: In step (1), the particle size of the ceramic powder is 100nm-10μm, preferably 300nm-10μm, and the specific surface area is 10-50m 2 / g.
5. The fixing method according to claim 3 or 4, characterized in that: In step (1), the mass ratio of the ceramic powder to dopamine hydrochloride is 5-10:
1.
6. The fixing method according to any one of claims 3 to 5, characterized in that: In step (1), the ratio of the raw material mixed powder to deionized water is 1g:5-10mL.
7. The fixing method according to any one of claims 3 to 6, characterized in that: In step (2), the mass ratio of the dopamine-loaded ceramic powder to amyloglucosidase is 1:0.1-0.
4.
8. The fixing method according to any one of claims 3 to 7, characterized in that: In step (2), the dosage ratio of the dopamine-loaded ceramic powder to deionized water is 1 g:5-50 mL, preferably 1 g:20-50 mL.
Citation Information
Patent Citations
A coaxial scaffold material with sustained-release function
CN113172887B
Natural biodegradable matrices and uses thereof
CN101316619A
Glucose biosensor material, preparation method and application
CN110987833A
Biological ceramic material as well as preparation method and application thereof
CN117069502A
Immobilized enzyme and method for converting maltooligoglucoside to glucoside
JP2002253229A